Comparative cephalogram study of Kim, Steiner and projections USP in determining the sagittal skeleton relationship - Acuña Diaz, Evelyn del Carmen (2011)
The objective of the present work was to compare the relationship skeletal sagital applying KIM’S cephalograms,Steiner and Projection USP. It was carried out the study cephalometric in 100 radiographs ofpatient without growth, with ages you enter 18 to 30 years of both genders; that they attended the clinicof orthodontics of the Unit of Post Grade of San Marcos University among the years 2005-2010. Tothe respective results they were applied the statistical test of Kappa to see the existence of agreement inwhat concerns to the skeletal relationship, among the analyses by means of their evaluation scale, besidescomparative charts. The results showed a level of low agreement among Steiner - Kim (Kappa: 0,283)Steiner - Projection USP (Kappa: 0,341) Kim-USP (Kappa: 0,277). The biggest coincidence one observesbetween the cephalograms of Steiner and Projection USP and the minor between Kim and USP.